Expression of IL-6 on Breast Cancer Mice Treated by Combination of Phyllanthus Urinaria and Catharanthus roseus Extract - Shofiyah, aya; Djati, Mohammad Sasmito; Rifa'i, Muhaimin (Biotropika: Journal of Tropical Biology, 2022)
Breast cancer is one kind of cancer that can cause the death in women. Although, many kind of treatment have done to suppress the growth of breast cancer case, but the number of case still increased. Chemotherphy is one kind of treatment used to suppress breast cancer case. But it is known that can give many poor effect. So it need to get an alternative treatment such as using a herbal plant as medicine as Phyllanthus urinaria and Catharanthus roseus. This research aimed to study the effect of Phyllanthus urinaria and Catharanthus roseus on IL-6 expressed by CD11bin breast cancer model.this research using RAL divided into 6 group as Normal group (N), cancer group (K), Cisplatin treatment (C), Dose 1 (D1) (Phyllanthus urinaria 500 mg/kg weight and Catharanthus roseus 15 mg/kg weight), dose 2 (D2) (Phyllanthus urinaria 1000 mg/kg weight and Catharanthus roseus 75 mg/kg weight) and dose 3 (D3) (Phyllanthus urinaria 2000 mg/kg weight and Catharanthus roseus 375 mg/kg weight). the mice had inject by DMBA in 0,015 mg/kg weight in six week. The combination of Phyllanthus urinaria and Catharanthus roseus were administrated orally in two weeks. The expression of IL-6 expressed by CD11b ws analysed by flow cytometry. Data analysed by SPPSS in one way ANOVA and tukey test. Based on result, it showed that dose 3 is the optimal dose to suppress the growth of cancer cells based on IL-6 expression. All of the dose used can suppress the growth of IL-6. Keywords: Breast cancer, Catharanthus roseus, IL-6, machrophage, Phyllanthus urinaria